2 fast 2 furious [videorecording (DVD)] - Singleton, John, 1968-2019-; Walker, Paul, 1973-2013; Tyrese; Mendes, Eva, 1974-; Hauser, Cole, 1975-; Ludacris (Rapper); Remar, James; Ealy, Michael; Thompson, Gary Scott (Universal, 2003)
Now an ex-cop on the run, Brian, hooks into outlaw street racing. When the Feds strong-arm him back, Brian's no rules, win-or-die skills are unleased against an international drug lord. With his velocity-addicted buddy riding shotgun, and a drop-dead-georgeous undercover agent dialing up the heat ... it becomes a desperate race for survival and justice.